Penatalaksanaan Holistik pada Anak Usia 6 Tahun dengan Tinea Kapitis melalui Pendekatan Kedokteran Keluarga di Wilayah Puskesmas Susunan Baru - Nova Sabila; Mayasari, Diana (CV. Jasa Sukses Abadi, 2024)
Dermatophytosis is a superficial infection caused by dermatophyte fungi. This infection is also often called tinea. Classification is based on the part of the body affected, namely tinea capitis (head), tinea faciei (face), tinea barbae (beard), tinea corporis (body), tinea manuum (hands), tinea cruris (groin), tinea pedis (legs), tinea unguinum (nails). The prevalence of dermatophytosis in Asia is 35.6%, while in Indonesia it is 52%. Tinea capitis is the first and most common infection that occurs in pre-school and school-age children when compared to other types of tinea with risk factors originating from exposure to the school environment and hygiene applied at home. The aim of implementing family doctor services based on evidence-based medicine for patients is to identify risk factors, clinical problems, and patient management based on a framework for solving patient problems using a patient centered and family approach. The data obtained were primary data obtained through autoanamnesis, alloanamnesis, physical examination, and home visits and secondary data obtained from the patient's medical records. Patient An. B aged 6 years as the age with the highest prevalence has internal risks, namely lack of knowledge, poor personal hygiene, and external factors found in the patient's environment. Management of patients holistically and comprehensively, patient-centered, family approach, and community-based in literature based on EBM. Interventions are provided medically and non-medically. Based on the evaluation results, it was found that there was an increase in knowledge, changes in clean and healthy lifestyles and understanding of disease.